Combined toxicity of polycyclic aromatic hydrocarbons and heavy metals to biochemical and antioxidant responses of free and immobilized Selenastrum capricornutum. (15th February 2013) - Wang, Ping; Luo, Lijuan; Ke, Lin; Luan, Tiangang; Tam, Nora Fung‐Yee
Abstract The aquatic environment often contains different groups of contaminants, but their combined toxicity on microalgae has seldom been reported. The present study compared the toxic effects of combined mixed polycyclic aromatic hydrocarbons (PAHs) and heavy metals on growth and antioxidant responses of free and immobilized microalga, Selenastrum capricornutum. Five PAHs—phenanthrene, fluorene, fluoranthene, pyrene, and benzo[a]pyrene—and four heavy metals at different concentrations—0.05 to 0.1 µg Cd2+ ml−1, 0.05 to 1 µg Cu2+ ml−1, 0.05 to 1 µg Zn2+ ml−1, and 0.5 to 2.5 µg Ni2+ ml−1—were examined. Results showed that the chlorophyll a content of free and immobilized S. capricornutum was not affected by PAHs but was significantly inhibited by heavy metals. Conversely, the antioxidant parameters, including the content of reduced glutathione (GSH) and the activities of superoxide dismutase and peroxidase, were significantly induced by both PAHs and metals. For the combined toxic effects of PAHs and heavy metals, cell growth and antioxidant responses varied with exposure time and contaminants and differed between free and immobilized cells. The effects of cocontaminants on the GSH content in free cells were mainly synergistic but changed to antagonistic in immobilized cells. The toxic effects of cocontamination on free cells were also more obvious than those on immobilized cells. These findings suggest that immobilization offers some protection to microalgal cells against toxic contaminants causing differences in the interaction and responses to combined toxicants between free and immobilized cells. Immobilized cells might be more suitable for treating wastewater containing toxic contaminants than free cells. Environ. Toxicol. Chem. 2013;32:673–683. © 2012 SETAC